The House system: Evaluating its role in the experience of business students. Issue 4 (4th July 2017) - Antoniadou, Marilena
ABSTRACT: This paper presents a case study of students' experiences of the House system, an innovative scheme introduced for business students, aiming to enhance student experience. The findings are based on a survey of 350 students and 4 group interviews. Analysis of the findings, both statistical and qualitative, indicated perceived clear benefits for the House system, including making friendships, being mentored by supportive staff and skills development. However, they also perceived disadvantages, particularly with regard to unawareness of the system, and limited extra-curriculum and employability activities. The paper concludes that active participation in the House system has a potentially useful role in creating a meaningful and collaborative environment amongst students and staff.